The economics and psychology of happiness : the LIFE framework and sustainable development - Ho, Lok-sang (Routledge, 2026)
"This book applies the analytical framework used by economists to investigate how one can make the most out of one's life, thus achieving happiness and fulfilment. Building upon the author's earlier work, this book blends the classic theories and empirical evidence of positive psychology with economic concepts of choice, capital, information costs, and household production. It includes topics including happiness at work, corporate life, and sustainable development, which are at the forefront of this interdisciplinary field. Every chapter is accompanied by a summary of key points, as well as reflective questions for students. This book will interest researchers and students in happiness economics and positive psychology, and anyone keen to learn more about living fuller, happier lives"-- Provided by publisher.